Recommended Reads: Environmental Children's Literature - A Catalyst for Taking Action - David Valente (CLELEjournal, 2021)
Bryon, Nathan & Adeola, Dapo (2020) Clean Up! Macfarlane, Robert & Morris, Jackie (2017) The Lost Words: A Spell Book Lerwill, Ben (2020) Climate Rebels Morpurgo, Michael (2020) The Puffin Keeper